Body Dissatisfaction and Somatic Complaints: The Mediating Role of Self-Criticism - Aghaziarati, Ali (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to investigate whether self-criticism mediates the relationship between body dissatisfaction and somatic complaints in adolescents. A descriptive correlational research design was employed with a sample of 413 high school students from Georgia, selected based on the Morgan and Krejcie sample size determination table. Participants completed three standardized self-report instruments: the Body Shape Questionnaire-16 (BSQ-16) for body dissatisfaction, the Levels of Self-Criticism Scale (LOSC) for self-criticism, and the Children’s Somatization Inventory (CSI-24) for somatic complaints. Data were analyzed using SPSS-27 for descriptive statistics and Pearson correlation coefficients, and AMOS-21 for Structural Equation Modeling (SEM) to assess model fit and test the hypothesized mediation model. Descriptive results showed moderate to high levels of body dissatisfaction (M = 56.74, SD = 11.29), self-criticism (M = 89.63, SD = 13.57), and somatic complaints (M = 38.12, SD = 8.41). Pearson correlations indicated significant positive associations between body dissatisfaction and self-criticism (r = .48, p < .001), body dissatisfaction and somatic complaints (r = .44, p < .001), and self-criticism and somatic complaints (r = .52, p < .001). The SEM model demonstrated good fit indices (χ²/df = 1.75, CFI = 0.96, RMSEA = 0.042). Path analysis revealed a significant direct effect of body dissatisfaction on somatic complaints (β = .25, p < .001), a significant indirect effect via self-criticism (β = .20, p < .001), and a total effect of β = .45 (p < .001), supporting partial mediation. The findings highlight self-criticism as a significant cognitive mechanism through which body dissatisfaction contributes to somatic complaints in adolescents. Interventions aimed at reducing self-critical thought patterns may help mitigate the negative physical and psychological effects of body dissatisfaction in youth.